Learning and teaching engineering design through modeling and simulation on a CAD platform. Issue 4 (28th June 2018) - Xie, Charles; Schimpf, Corey; Chao, Jie; Nourian, Saeid; Massicotte, Joyce
Abstract: This paper provides a theoretical perspective of how modeling and simulation on a CAD platform can be used to teach science concepts and inform design decisions. The paper discusses the educational implications of three recent advancements in CAD technologies: system integration, machine learning, and computational design. The challenges to design energy‐efficient buildings that harness solar energy are used as the engineering examples to illustrate the learning and teaching opportunities created by the modeling, simulation, and data mining capabilities of the Energy3D software, which is a CAD tool developed from scratch along the directions of the three advancements to support engineering research and education. Preliminary results from students in a physics classroom and an online course shed light on the effects of these features on guiding student to design cost‐effective rooftop solar power systems for their own home buildings.